Surgical treatment options of displaced midshaft fractures of the clavicle in young adults: plate fixation versus intramedullary nailing - Ji Un Kim; Ji Young Yoon; Hyung Jun Park; Jung Ho Park (Clinics in Shoulder and Elbow)
Background This study aimed to compare the outcomes and complications of active young adults undergoing open reduction and plate fixation (ORPF) and intramedullary nailing (IMN) for displaced midshaft clavicle fractures (MCFs). Methods A retrospective review was performed on all patients undergoing ORPF and IMN of complete MCFs at a single center between 2018 and 2022. Patients who were younger than 60 years with radiographic follow-up until union were included in the study. The mean age of the patients was 33.1 years. Outcome measures were achievement of union, time to healing, residual deformity, complications, and need for additional procedures. Results Of 39 patients, 29 underwent ORPF and 10 underwent IMN. Plate fixation provided faster functional recovery in the first 6 months, but no difference was observed after 1 year. All fractures in the IMN group healed (100%), compared to 90% in the ORPF group (P=0.08). Mean time to union was 21±8.9 weeks and was significantly different between the two groups (P<0.01), with the ORPF group averaging 23.1 weeks and the IMN group 20.8 weeks. Nonunion rates were higher in the ORPF group (10.3%) than in the IMN group (0%), but the difference was not significant (P=0.08). Conclusions Both methods restored patients to their pre-injury functional levels. However, IMN, with its higher healing rate, fewer required revision surgeries, and lower incisional numbness, appears to be the preferred method for treating MSFs without comminution in young adults. Level of evidence III.